A study on experience renewal design of public space in ancient towns under the Perspective of scene theory - Ying Liu; Xiduo Yi; Huihui Liang (Journal of Asian Architecture and Building Engineering, 2025)
The engagement of users in public spaces is pivotal for the vitality and enduring progress of ancient towns. This research develops a theoretical framework to understand the determinants of user participation in these spaces, drawing on Scene Theory and Stimulus-Organism-Response theory(SOR). Employing structural equation modeling (SEM) and fuzzy set qualitative comparative analysis (fsQCA), the study examines 314 valid samples. Findings indicate that service quality, distinctive experiences, perceptual cognition, and cultural understanding significantly impact user satisfaction, enjoyment, and sense of belonging, thereby shaping their active participation. The necessity test reveals that no single factor can fully account for the mechanisms underlying active user engagement; instead, a synergistic effect of multiple conditions is necessary. Through this analysis, three potent combinations of conditions are identified that foster sustained active participation among users. The study applies these insights to the public space design of Nanquan Ancient Town in Wuxi, distilling design strategies for the perceptual pleasure scene, the diversified experience scene, and the cultural belonging scene. These findings offer actionable recommendations for enhancing scene creation in ancient town public spaces, with the goal of improving user experience and participation, and informing strategic decision-making.